The Effect of Ethanol and Water Fuel Mixture in Direct Injection Diesel Engine on Power and Specific Fuel Consumption - Akhmad Nafii; Irawan , Bambang (Evrimata: Journal of Mechanical Engineering, 2024)
The increasing use of fossil energy is causing a national and global energy crisis. To reduce dependence on fossil energy, planned actions are being taken to replace fossil energy with alternative energy sources, one of the alternative fuels that can be burned is ethanol or ethyl alcohol. This research aims to identify the effect of using a mixture of ethanol and water fuel, by controlling the ethanol content and the effect of engine speed on power and specific fuel consumption in direct injection engines, as well as identifying the interaction between ethanol content and engine speed. This research uses an experimental method by testing a direct injection engine connected to an  electric generator to determine power and SFC by testing variations in ethanol content and engine speed. For the load in this test, 3 250 Watt lamps are used. The result was that when testing the direct injection engine using a 93% ethanol fuel mixture it produced a power of 0.115 kW at 1300 rpm, while in the 96% ethanol test the power obtained was 0.118 kW at the same engine speed. For an ethanol content of 99% at 1900 engine speed, the highest power is obtained, reaching 2,326 kW, this indicates that the higher the ethanol content used, the greater the power produced. However, the SFC value has decreased. As in testing 93% ethanol content at 1300 engine speed, the SFC obtained was 2.2997 L/kWh. At 99% ethanol content, SFC experienced a minimum decrease of 0.6418 /kWh. At low ethanol levels, the water content tends to be high which causes the combustion process to be incomplete.